Incarceration and its effects toward family functioning across the family life cycle selected case of new bilibid prison inmates in Muntinlupa City, Philippines - Lobo, Kristine Gail C.; Dy, Marison R. (2012)
This study aimed to determine the effects of incarceration on family functioning based on family life cycle (FLC) stages as experienced by inmates. A qualitative research design was used to look into the lives of five medium security prisoners who are currently enrolled in baccalaureate programs. In-depth interviews were conducted to develop the respondents' cases representing each FLC stage. Findings showed that in the Beginning Family stage, the inmate's emotional aspect is the main concern because his family of orientation cannot visit him. Despite this, the inmate and his wife focused on building their own family. In the Child Bearing Stage, the problem was observed with the inmate's financial aspect because he cannot provide adequately for his own family. Still, the family members managed to reorganize and redifine their roles to remain functioning as a family. At the end of Child Bearing Stage, the problem was observed with the inmate's financial aspect because he cannot provide adequately for his own family. Still, the family members managed to reorganize and redefine their roles to remain functioning as a family. At the end of Child Bearing Stage, the inmate is concerned with the emotional and economic aspects because he cannot perform his financial obligations to his family. As a result, the family became dysfunctional due to their emotional distancing. Furthermore, in the Empty Nest and Family Dissolution Stages, their problems were also on the emotional and financial aspects. Both inmates experienced abandonment from their families and financial difficulties inside the prison. Family intervention programs for the family left behind by the inmates need to be considered as part of the rehabilitation programs offered by the government so that while the inmate is rehabilitated within, the family is also supported in coping with the father's incarceration.
Keywords: Prisoners; Rehabilitation